Creating an in-vitro model system for studying phase separation in virus assembly - Wiener, Katharina (Jihočeská univerzita, 2021)
This thesis focuses on the study of the ?NS protein of the avian reovirus and as this virus is causing considerable annual losses in the poultry industry, understanding its replicative cycle on a molecular basis is highly anticipated. One area of interest is hereby the formation of so-called viroplasms via liquid-liquid phase separation (LLPS) of the ?NS protein. The exact processes involved in LLPS, however, remain mostly unknown. By establishing an in-vitro model system we tried to elucidate the environmental conditions needed for phase separation, in order to gain a better understanding of the viral replicative cycle, as well as LLPS in general.
Creating an in-vitro model system for studying phase separation in virus assembly
Keywords: avian reovirus; viral replication; liquid-liquid phase separation; viroplasms; soluble protein production; fluorescence spectroscopy; protein crystallization; avian reovirus; viral replication; liquid-liquid phase separation; viroplasms; soluble protein production; fluorescence spectroscopy; protein crystallization